Association between anticholinergic burden and hospital readmission in older patients: a prospective analysis. Issue 2 (15th March 2021) - Castier, Sophie; Preda, Cristian; Puisieux, François; Beuscart, Jean-Baptiste; Mahmoudi, Rachid; Visade, Fabien
ABSTRACT: Objective: Despite known adverse effects of anticholinergic (AC) medication, little work has been devoted to the impact of high anticholinergic burden on the rate of hospital readmission. The purpose of this study was to analyze prospectively the link between high AC burden and the rate of all-cause thirty-day hospital readmission in older people. Study design: This was a prospective non-interventional study conducted from January to August 2019 in one acute-care geriatric ward. All hospital stays of patients aged at least 75 years who were discharged to their home were included in the analysis. AC burden was determined from discharge prescriptions using the Anticholinergic Drug Scale (ADS) and the Anticholinergic Risk Scale (ARS), and defined as high if ≥3. Results: The analysis concerned 350 hospital stays. Median patient age was 88 years (interquartile interval 84–91). In a multivariate analysis, the risk of hospital readmission within 30 days was not increased for patients with high AC burden (ADS≥3): odds ratio 1.16 [95% confidence interval 0.56–2.37], compared to a patient whose anticholinergic burden was not high. Conclusion: Unlike retrospective studies on this issue, the findings of our prospective analysis do not support a higher risk of hospital admission within 30 days for older people with high AC burden as assessed from their discharge prescriptions.